The unexpected mechanism of transformation from conventional room-temperature phosphorescence to TADF-type organic afterglow triggered by simple chemical modification. Issue 6 (26th January 2023) - Wu, Minjian; Li, Jiuyang; Huang, Ju; Wang, Xuepu; Wang, Guangming; Chen, Xiuzheng; Li, Xun; Chen, Xuefeng; Ding, Shuhui; Zhang, Hefeng; Zhang, Kaka
Abstract : This study presents the mechanism of transformation of afterglow induced by specific chemical reactions. Consequently, highly efficient red TADF-type afterglow materials that counteract with the energy gap law have been achieved. Abstract : The study of transformation of photophysical behaviours in organic afterglow systems has emerged as an important topic, whereas the transformation in the reported studies only gives change of afterglow colour, duration or intensity. Herein, we report a serendipitous finding of the mechanism of afterglow transformation from conventional RTP to TADF-type organic afterglow triggered by simple chemical modification of coronene systems; usually, chemical modification can only lead to spectral shifts of luminescent systems. Coronene molecules show typical RTP behaviours when doped in organic matrices. After being substituted by difluoroboron β-diketonate moieties, the coronene-containing materials exhibit a TADF-type organic afterglow mechanism, which features a moderate k RISC to harvest triplet energies, enhance afterglow efficiency, and maintain long afterglow lifetimes. Interestingly, the TADF-type afterglow materials can be excited by visible lights, possess emission wavelength > 600 nm and PLQY > 40%, display excellent processability into desired patterns and aqueous dispersion, and function as high-contrast in vivo bioimaging agents. The present study provides a unique pathway for the manipulation of triplet excited states to fabricate high-performance organic afterglow materials.